Traditional Japanese Herbal Medicine Hochu-Ekki-to Promotes Pneumococcal Colonization Clearance via Macrophage Activation and Interleukin 17A Production in Mice - Nakakubo, Sho; Kimura, Soichiro; Mimura, Kazuyuki; Kajiwara, Chiaki; Ishii, Yoshikazu; Konno, Satoshi; Tateda, Kazuhiro (Frontiers in Cellular and Infection Microbiology, 2020)
Streptococcus pneumoniae may colonize the nasopharynx, and as pneumococcal colonization causes invasive diseases and the subsequent transmission, reducing bacterial burden in the nasal cavity is critical. Hochu-ekki-to (TJ-41) is a traditional Japanese herbal medicine that exerts immunomodulatory effects in host cells. In this study, we investigated the potency of TJ-41 in modulating pneumococcal colonization clearance by activating host immunity. Mice, intranasally inoculated with pneumococci, were treated orally with TJ-41. During colonization, TJ-41 treatment significantly reduced pneumococcal burden and increased macrophage population in the nasopharynx. Furthermore, interleukin 17A production was significantly enhanced after TJ-41 treatment. In vitro experiment using nasal-derived cells revealed that pneumococcal antigen exposure upregulated the transcription of interleukin 17A in the TJ-41-treated group compared with that in the control group. Macrophages activated by killed bacteria were significantly increased in the presence of TJ-41 in an interleukin 17A-dependent manner. Moreover, TJ-41 enhanced phagocytosis, inhibited bacterial growth, and improved the antigen-presenting capacity of macrophages. Our results demonstrate that TJ-41 accelerates the clearance of pneumococcal nasopharyngeal colonization via macrophage activation. Subsequent production of interleukin 17A provides an additional benefit to effector cells.